Agrarian Conflict in Aceh: The Intersection of Corporate Interests, Farmers' Rights, and Government Governance - Muthallib, Abdul (State of Islamic Institute Langsa, 2025)
Ideally, agrarian conflicts in Aceh could be resolved with a fair and sustainable approach that accommodates the interests of companies, farmers' rights, and the role of the government in transparent governance. However, in reality, these conflicts are often triggered by inequalities in land rights distribution, injustice in the treatment of farmers, and the lack of effective oversight of companies, as well as government policies that do not always favor local communities' interests. This study aims to analyze the dynamics of agrarian conflicts in Aceh, focusing on the interactions between the interests of companies, farmers' rights, and the role of government governance, as well as identifying the factors influencing the inequality in land dispute resolution. The methodology used in this study is qualitative literature-based research with a descriptive analysis approach. The results of the study conclude that agrarian conflicts in Aceh are caused by imbalances in land control between companies, farmers, and the government, with the interests of companies often clashing with farmers' rights, while government governance has not yet been able to accommodate all parties fairly. Resolving these conflicts requires a holistic approach that strengthens agrarian reform policies, oversight of companies, and transparent dispute resolution mechanisms, followed by the active role of indigenous communities and advocacy organizations in protecting farmers' rights.